Monocrystal lithium nickel manganese oxide synthesized by multi-stage stepped sintering method and preparation method of monocrystal lithium nickel manganese oxide
Synthesis of single-crystalline nickel-manganese oxide through multi-stage step-by-step sintering method solves the problem of structural failure and unstable circulation performance of traditional polycrystalline high-voltage nickel-manganese oxide under high voltage, and achieves higher mechanical strength and circulation performance.
Patent Information
- Application Number
- CN202510240885.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-03
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-03-03
AI Technical Summary
Traditional polycrystalline high voltage lithium nickel manganate is prone to structural damage and electrochemical losses under high voltage, resulting in unstable cycling performance.
Single-crystalline nickel-manganese oxide is synthesized by multi-stage step-by-step sintering method. Through various heating methods such as infrared radiation, combustion aids and microwave heating, the temperature curve is controlled to show multiple step-like characteristic peaks, which promotes the relative growth of (100) and (110) crystal planes.
The mechanical strength and circulation performance of single-crystal nickel-manganate cathode material are improved, the high-temperature shelving performance of the battery is enhanced, and the crystal defects and surface oxygen defects of the material are reduced.
Smart Images

Figure CN119736697A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion battery positive electrode materials, in particular to single crystal lithium nickel manganese oxide synthesized by a multi-stage stepped sintering method and a preparation method thereof. Background Art
[0002] Traditional polycrystalline high-voltage lithium nickel manganese oxide generally exhibits irreversible structural and electrochemical losses under high voltage, which greatly reduces its stability. Micron-sized "secondary" particles are usually composed of many "primary" nanoparticles, allowing the electrolyte to penetrate into the interior through the gaps between the grains. The random crystal orientation of the primary particles can cause great stress during the cycle, resulting in cracks. Especially in the fully charged state, due to the anisotropy of the lattice contraction, local stress is generated along the grain boundaries, causing structural damage, and even microcracks will form between the grains during the first stage of charging. The electrolyte penetrates through the microcracks, causing the inside of the battery positive electrode to be in direct contact with the electrolyte. These microcracks destroy the mechanical integrity of the positive electrode material and promote its volume change and the generation of cracks, further destroying the cycle performance of the material and reducing the efficiency of the positive electrode electrochemical reaction. However, Li + and Ni 4+ The degree of mixing inside the lattice is serious, which makes it easier to produce microcracks inside the crystal. Therefore, inhibiting the generation of microcracks is the key to improving the mechanical strength of lithium nickel manganese oxide positive electrode materials and inhibiting the rapid attenuation of material capacity.
[0003] Research has found that single-crystal lithium nickel manganese oxide has micron-sized particles. The "single crystal" morphology limits surface reactions and particle cracking, has the advantages of resistance to mechanical fracturing and gas precipitation, and can improve the cycle and thermal stability of the battery. Single crystals can completely eliminate inter-particle stress, there are no grain boundaries for electrolyte penetration, and also reduce the channels for atomic oxygen to diffuse from the inside of the material to the outside. Another benefit is the high density. Not only does the crystal itself have no pores, but it can also withstand greater forces without breaking during the rolling process. Therefore, single crystal morphology with a specific crystal plane advantage has excellent high-voltage stability, high mechanical strength and stable structure, and is expected to be used to solve the problems of structural damage and cycle performance under high pressure of traditional polycrystalline high-voltage lithium nickel manganese oxide materials.
[0004] For example, patent CN201611029096X discloses a large single crystal lithium nickel manganese oxide positive electrode material and its preparation method, patent CN2019106224263 discloses a preparation method of a micron-sized single crystal lithium nickel manganese oxide positive electrode material, patent CN2022116125073 discloses a preparation method of a chamfered single crystal lithium nickel manganese oxide positive electrode material, and patent CN2023109510687 discloses the preparation of a single crystal lithium nickel manganese oxide positive electrode material with specific crystal surface exposure. None of the above schemes involve the specific process of directional growth of the dominant interface of single crystal lithium nickel manganese oxide. The stability of single crystal lithium manganese oxide in the synthesis process under the condition of voltage greater than 4.8V needs to be further improved, and the cycle performance of the lithium nickel manganese oxide positive electrode material in the 3.0-4.9V cycle process cannot be improved. Those skilled in the art are in urgent need of developing a single crystal lithium nickel manganese oxide synthesized by a multi-stage sintering method and its preparation method to meet the existing application market and performance requirements. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a single crystal lithium nickel manganese oxide synthesized by a multi-stage stepped sintering method and a preparation method thereof, the purpose of which is to solve the generation of microcracks inside the lithium nickel manganese oxide positive electrode material, improve the mechanical strength of the lithium nickel manganese oxide positive electrode material, and improve the battery cycle performance and high-temperature shelf performance.
[0006] In order to achieve the above object, a technical solution adopted by the present invention is: A single crystal lithium nickel manganese oxide synthesized by a multi-stage stepped sintering method, the preparation method of the single crystal lithium nickel manganese oxide comprising the following steps: (1) mixing a combustion aid, a lithium salt and a lithium nickel manganese oxide precursor uniformly according to a molar ratio to obtain a mixed raw material; (2) In the first stage, infrared radiation heating is used to raise the temperature to T1, and the heating time is t1, so that the mixed raw materials are accelerated to discharge free water and crystal water contained in the mixed raw materials, and the infrared radiation heating is turned off to reduce the temperature of the mixed raw materials; (3) In the second stage, the combustion aid is used to generate an oxidation reaction, which releases a large amount of heat and raises the temperature of the mixed raw materials to T2. The heating time is t2, which accelerates the discharge of carbon dioxide gas from the mixed raw materials. After the reaction is completed, the temperature of the mixed raw materials decreases. (4) In the third stage, microwave heating is used to raise the temperature to T3, and the heating time is t3, so that the growth of the (100) and (110) crystal planes of lithium nickel manganese oxide is accelerated; (5) After turning off the microwave heating, controlling the sintering temperature of the mixed raw materials to carry out the synthesis reaction; (6) In the cooling stage, microwave heating or infrared heating is used to raise the temperature to 800°C. After cooling, single crystal lithium nickel manganese oxide synthesized by a multi-stage step-by-step sintering method is obtained.
[0007] Preferably, in (1), the molar ratio of the combustion aid, the lithium salt and the lithium nickel manganese oxide precursor is 0.001-0.1:0.48-0.58:1.
[0008] Preferably, in (1), the combustion aid is one of bioethanol, biobutanol, phosphate ester, triethyl phosphate, microcrystalline wax, liquid paraffin, liquid resin, polyethylene wax, glycerol, glycerol fatty acid, biodiesel, and carbon powder.
[0009] Preferably, in (2), during the infrared heating process, the infrared radiation wavelength is 200 μm-1 μm, the heating rate is 10-80°C / s, and the instantaneous heat flux density is 0.01-1 MW / m 2 Preferably, the infrared radiation wavelength is 50 μm-2 μm, the heating rate is 20-50 ° C / s, and the instantaneous heat flux density is 0.1-0.5 MW / m 2 More preferably, the infrared radiation wavelength is 20 μm-2.5 μm, the heating rate is 20-40 ° C / s, and the instantaneous heat flux density is 0.2-0.4 MW / m 2 , T1 is 150-300℃, t1 is 0.1-1h.
[0010] Preferably, in (3), the combustion aid heating temperature T2 is 700-950° C., and the heating time t2 is 0.01-0.2 h.
[0011] Preferably, in (4), the microwave heating temperature T3 is 750-1200° C., and the heating time t3 is 0.1-2 h.
[0012] Preferably, in (5), the sintering temperature is 820-980° C., and the synthesis reaction time is 12-24 h.
[0013] Preferably, the preparation temperature curve presents multiple step-like characteristic peaks, that is, multiple stages of rapid temperature rise and temperature drop of the material occur during the heating process, the total heating time of the synthesis is t, the synthesis temperature is T; the first stage time is t1, the highest temperature is T1, the second stage time is t2, the highest temperature is T2, the Nth stage time is t n , the maximum temperature is T n , satisfying the following relationship: T1×t≥T×t1, T2×t≥T×t2, ..., T n ×t≥T×t n , where 2≤n≤3.
[0014] Preferably, the total heating time t is 3-20 h, and the synthesis temperature T is 600-1200° C., and more preferably the total heating time t is 6-10 h, and the synthesis temperature T is 800-1000° C.
[0015] Preferably, the method used in the heating and temperature raising is one or more of electric heating, infrared radiation heating, microwave heating, combustion aid heating, heat flow heating, and Joule heat heating.
[0016] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art: Generally, the sintering curve of lithium nickel manganese oxide positive electrode material is a trapezoid. The raw material is heated from room temperature to the sintering temperature at a fixed heating rate, and then cooled naturally after sintering for a certain period of time. After cooling, the lithium nickel manganese oxide positive electrode material is obtained. Uniform heating and cooling rate is not conducive to obtaining disordered lithium nickel manganese oxide. The electronic conductivity of disordered spinel is 2-3 orders of magnitude higher than that of ordered spinel. Therefore, disordered lithium nickel manganese oxide has better rate performance and is suitable for charging and discharging at high rates. The electrochemical properties of lithium nickel manganese oxide are closely related to the crystal planes exposed on the surface of the material. The (111) crystal plane is dominated by tightly packed oxygen atoms and is the dominant growth interface of the spinel structure; the (100) crystal plane has a moderate distribution of Mn, Ni and Li metal ions on the surface, which can avoid the deterioration of cycle performance caused by excessive dissolution of Mn; the (110) crystal plane has a large number of ion channels, which can increase the migration rate of lithium ions. The multi-stage stepped sintering method can rapidly heat up and cool down the material, and the relative growth rate of the (100) and (110) crystal planes can be increased by rapid temperature changes, thereby increasing the proportion of the (100) and (110) crystal planes on the material surface, thereby improving the cycle performance and rate performance of the single crystal lithium nickel manganese oxide positive electrode material.
[0017] The single crystal lithium nickel manganese oxide synthesized by the multi-stage stepped sintering method and the preparation method thereof of the present invention also have other beneficial effects. 1) Because the medium-wave infrared radiator has a high heating efficiency for water-containing materials, the medium-wave infrared radiation can be well absorbed by water and directly converted into heat, thereby accelerating the evaporation of water and the drying of the material. Therefore, using infrared radiation heating to make the raw materials infrared radiation can accelerate the evaporation of free water and crystal water in the raw materials, and can also make Ni 0.25 Mn 0.75 1) In the heating process, the heat generated by the combustion of the combustion aid is used to quickly heat the mixed raw materials to 650-950°C, so that the lithium carbonate is quickly decomposed and CO2 gas is discharged. 2) In the heating process, microwave heating is used to quickly increase the temperature of the mixed raw materials to 750-1200°C, increase the relative growth rate of the (100) and (110) crystal planes of lithium nickel manganese oxide, and increase the proportion of (100) and (110) crystal planes on the surface of the material. 3) In the cooling process, microwave heating or infrared heating is used to heat the material again to release the lattice stress inside the material and reduce the crystal defects and surface oxygen defects of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 It is the temperature curve of the preparation process of Example 1. It can be seen from the figure that the preparation temperature curve presents multiple step-like characteristic peaks; Figure 2 This is a scanning electron microscope image of single-crystal lithium nickel manganese oxide prepared in Example 1. It can be seen from the image that the lithium nickel manganese oxide has a single crystal morphology, and obvious (100) and (110) crystal planes can be observed on the surface; Figure 3 The temperature curve of the preparation process of Comparative Example 1. It can be seen from the figure that the preparation temperature curve is trapezoidal; Figure 4 This is a scanning electron microscope image of the single crystal lithium nickel manganese oxide of Comparative Example 1. It can be seen from the figure that the prepared lithium nickel manganese oxide has a polycrystalline morphology, and an obvious (111) crystal plane can be observed on the surface, and the (100) and (110) crystal planes account for a very small proportion and are not obvious; Figure 5 A comparison chart of the cycle performance curves of the batteries was prepared for Example 1, Comparative Example 1 and Comparative Example 2. DETAILED DESCRIPTION
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the specific implementation methods of the present invention will be described below with reference to the accompanying drawings. Obviously, the embodiments described below are only some embodiments of the present invention, and for ordinary technicians in this field, other implementation methods can be obtained based on these embodiments without creative work. Embodiment 1
[0020] (1) Triethyl phosphate combustion aid, Li2CO3 and Ni 0.25 Mn 0.75 (OH)2 was mixed uniformly in a molar ratio of 0.003:0.25:1 to obtain a mixed raw material; (2) In the first stage, the temperature was raised to 150°C using infrared radiation heating method, and the heating time was 0.5 h. The infrared radiation wavelength was 20 μm, the heating rate was 40°C / s, and the instantaneous heat flux reached 0.3 MW / m 2 , accelerate the discharge of Ni 0.25 Mn 0.75 (OH)2 contains free water and crystal water. Turn off the infrared radiation heating to reduce the temperature of the mixed raw materials. When the temperature drops to 90°C, continue to heat up; (3) In the second stage, triethyl phosphate is used to undergo an oxidation reaction, which releases a large amount of heat and rapidly raises the temperature of the mixed raw material to 700°C. The heating time is 0.01h, which accelerates the discharge of carbon dioxide gas from the mixed raw material. After the reaction is completed, the temperature of the mixed raw material decreases to 240°C and continues to rise; (4) In the third stage, when the temperature of the mixed raw materials is raised to 800°C, microwave heating is used to raise the temperature to 1000°C for 2 hours to accelerate the growth of the (100) and (110) crystal planes of lithium nickel manganese oxide; (5) The total heating time was controlled to be 6 h. After the microwave heating was turned off, the sintering temperature of the mixed raw materials was controlled to be 900 °C and the synthesis reaction was carried out for 16 h. (6) In the cooling stage, microwave heating is used to raise the temperature to 800°C. After cooling, single crystal lithium nickel manganese oxide synthesized by a multi-stage step-by-step sintering method is obtained. Embodiment 2
[0021] (1) Bioethanol, Li2CO3 and Ni 0.25 Mn 0.75 (OH)2 was mixed uniformly in a molar ratio of 0.002:0.25:1 to obtain a mixed raw material; (2) In the first stage, the temperature was raised to 300°C by infrared radiation heating method, and the heating time was 1h. The infrared radiation wavelength was 5μm, the heating rate was 30°C / s, and the instantaneous heat flux reached 0.2MW / m 2 , accelerate the discharge of Ni 0.25 Mn 0.75 (OH)2 contains free water and crystal water. Turn off the infrared radiation heating to reduce the temperature of the mixed raw materials. The temperature is reduced to 140°C and the temperature is continued to rise; (3) In the second stage, bioethanol is used for oxidation reaction, which releases a large amount of heat and rapidly raises the temperature of the mixed raw material to 950°C. The heating time is 0.01h, which accelerates the discharge of carbon dioxide gas from the mixed raw material. After the reaction is completed, the temperature of the mixed raw material decreases to 400°C and continues to increase. (4) In the third stage, when the temperature of the mixed raw materials is raised to 850°C, microwave heating is used to raise the temperature to 1000°C for 1 hour to accelerate the growth of the (100) and (110) crystal planes of lithium nickel manganese oxide; (5) The total heating time was controlled to be 8 h. After the microwave heating was turned off, the sintering temperature of the mixed raw materials was controlled to be 900 °C and the synthesis reaction was carried out for 18 h. (6) In the cooling stage, infrared heating is used to raise the temperature to 700°C. After cooling, single crystal lithium nickel manganese oxide synthesized by a multi-stage step-by-step sintering method is obtained. Embodiment 3
[0022] (1) Microcrystalline wax, glycerol fatty acid, Li2CO3 and Ni 0.25 Mn 0.75 (OH)2 was mixed uniformly in a molar ratio of 0.0005:0.0005:0.25:1 to obtain a mixed raw material; (2) In the first stage, the temperature was raised to 200°C using infrared radiation heating method, and the heating time was 0.5h. The infrared radiation wavelength was 40μm, the heating rate was 100°C / s, and the instantaneous heat flux reached 0.4MW / m 2 , accelerate the discharge of Ni 0.25 Mn 0.75 (OH)2 contains free water and crystal water. Turn off the infrared radiation heating to reduce the temperature of the mixed raw materials. When the temperature drops to 100°C, continue to heat it up; (3) In the second stage, microcrystalline wax and glycerol fatty acid undergo oxidation reaction, which releases a large amount of heat and rapidly raises the temperature of the mixed raw materials to 800°C. The heating time is 0.1h, which accelerates the discharge of carbon dioxide gas from the mixed raw materials. After the reaction is completed, the temperature of the mixed raw materials decreases to 415°C and continues to rise; (4) In the third stage, when the temperature of the mixed raw materials is raised to 850°C, microwave heating is used to raise the temperature to 1000°C for 2 hours to accelerate the growth of the (100) and (110) crystal planes of lithium nickel manganese oxide; (5) The total heating time was controlled to be 10 h. After the microwave heating was turned off, the sintering temperature of the mixed raw materials was controlled to be 950 °C and the synthesis reaction was carried out for 12 h. (6) In the cooling stage, infrared heating is used to raise the temperature to 800°C. After cooling, single crystal lithium nickel manganese oxide synthesized by a multi-stage step-by-step sintering method is obtained. Embodiment 4
[0023] (1) Polyethylene wax, carbon powder, LiOH·H2O and Ni 0.25 Mn 0.75 O are mixed uniformly according to a molar ratio of 0.0002:0.0001:0.51:1 to obtain a mixed raw material; (2) In the first stage, the temperature was raised to 300°C using infrared radiation heating method for 1 hour. The infrared radiation wavelength was 100 μm, the heating rate was 60°C / s, and the instantaneous heat flux reached 0.25 MW / m 2 , so that the mixed raw materials are accelerated to discharge the free water and crystal water contained in the mixed raw materials, turn off the infrared radiation heating to reduce the temperature of the mixed raw materials, reduce the temperature to 160°C, and continue to heat up; (3) In the second stage, polyethylene wax and carbon powder undergo an oxidation reaction, which releases a large amount of heat and rapidly raises the temperature of the mixed raw materials to 1000°C. The heating time is 0.1h, which accelerates the discharge of carbon dioxide gas from the mixed raw materials. After the reaction is completed, the temperature of the mixed raw materials decreases to 605°C and continues to rise; (4) In the third stage, when the temperature of the mixed raw material is raised to 750°C, the temperature of the mixed raw material is rapidly raised to 1000°C for 0.5 h to accelerate the growth of the (100) and (110) crystal planes of lithium nickel manganese oxide; (5) The total heating time was controlled to be 6 h. After the microwave heating was turned off, the sintering temperature of the mixed raw materials was controlled to be 850 °C and the synthesis reaction was carried out for 20 h. (6) In the cooling stage, infrared heating is used to raise the temperature to 600°C. After cooling, single crystal lithium nickel manganese oxide synthesized by a multi-stage step-by-step sintering method is obtained. Embodiment 5
[0024] (1) Glycerol, triethyl phosphate, Li2CO3 and Ni 0.25 Mn 0.75 (OH)2 was mixed uniformly in a molar ratio of 0.005:0.01:0.26:1 to obtain a mixed raw material; (2) In the first stage, the temperature is raised to 200°C by infrared radiation heating method, and the heating time is 0.5h. The infrared radiation wavelength is 20μm, the heating rate is 50°C / s, and the instantaneous heat flux density reaches 0.15MW / m 2 , accelerate the discharge of Ni 0.25 Mn 0.75 (OH)2 contains free water and crystal water, and infrared radiation heating is used to reduce the temperature of the mixed raw materials. The temperature is reduced to 160°C and then continues to rise; (3) In the second stage, glycerol and triethyl phosphate are used to undergo an oxidation reaction, which releases a large amount of heat and rapidly raises the temperature of the mixed raw materials to 950°C. The heating time is 0.2h, which accelerates the discharge of carbon dioxide gas from the mixed raw materials. After the reaction is completed, the temperature of the mixed raw materials decreases to 550°C and continues to rise; (4) In the third stage, when the temperature of the mixed raw materials is raised to 800°C, microwave heating is used to raise the temperature to 1050°C for 0.1 h to accelerate the growth of the (100) and (110) crystal planes of lithium nickel manganese oxide; (5) The total heating time was controlled to be 3 h. After the microwave heating was turned off, the sintering temperature of the mixed raw materials was controlled to be 900 °C and the synthesis reaction was carried out for 15 h. (6) In the cooling stage, microwave heating is used to raise the temperature to 750°C. After cooling, single crystal lithium nickel manganese oxide synthesized by a multi-stage step-by-step sintering method is obtained. Embodiment 6
[0025] (1) Triethyl phosphate, Li2CO3 and Ni 0.25 Mn 0.75 (OH)2 was mixed uniformly in a molar ratio of 0.06:0.255:1 to obtain a mixed raw material; (2) In the first stage, the temperature was raised to 250°C by infrared radiation heating, and the heating time was 0.2h. The infrared radiation wavelength was 10μm, the heating rate was 50°C / s, and the instantaneous heat flux reached 0.3MW / m 2 , accelerate the discharge of Ni 0.25 Mn0.75 (OH)2 contains free water and crystal water. Turn off the infrared radiation heating to reduce the temperature of the mixed raw materials. The temperature is reduced to 180°C and the temperature is continued to rise; (3) In the second stage, triethyl phosphate undergoes an oxidation reaction, releasing a large amount of heat and rapidly raising the temperature of the mixed raw material to 700°C. The heating time is 0.01h, which accelerates the discharge of carbon dioxide gas from the mixed raw material. After the reaction is completed, the temperature of the mixed raw material decreases to 480°C and continues to rise; (4) In the third stage, when the temperature of the mixed raw materials is raised to 800°C, microwave heating is used to raise the temperature to 1200°C for 1 hour to accelerate the growth of the (100) and (110) crystal planes of lithium nickel manganese oxide; (5) The total heating time was controlled to be 20 h. After the microwave heating was turned off, the sintering temperature of the mixed raw materials was controlled to be 980 °C and the synthesis reaction was carried out for 15 h. (6) In the cooling stage, microwave heating is used to raise the temperature to 800°C. After cooling, single crystal lithium nickel manganese oxide synthesized by a multi-stage step-by-step sintering method is obtained. Embodiment 7
[0026] (1) Liquid resin, triethyl phosphate, Li2CO3 and Ni 0.25 Mn 0.75 (OH)2 was mixed uniformly in a molar ratio of 0.001:0.01:0.25:1 to obtain a mixed raw material; (2) In the first stage, the infrared radiation heating method was used to heat the temperature to 250°C, and the heating time was 0.1h. The infrared radiation wavelength was 40μm, the heating rate was 80°C / s, and the instantaneous heat flux reached 0.4MW / m 2 , accelerate the discharge of Ni 0.25 Mn 0.75 (OH)2 contains free water and crystal water. Turn off the infrared radiation heating to reduce the temperature of the mixed raw materials. When the temperature drops to 120°C, continue to heat up; (3) In the second stage, liquid resin and triethyl phosphate are used to undergo an oxidation reaction, which releases a large amount of heat and rapidly raises the temperature of the mixed raw materials to 950°C. The heating time is 0.1h, which accelerates the discharge of carbon dioxide gas from the mixed raw materials. After the reaction is completed, the temperature of the mixed raw materials decreases to 550°C and continues to rise; (4) In the third stage, when the temperature of the mixed raw materials is raised to 800°C, microwave heating is used to raise the temperature to 1100°C for 0.5 h to accelerate the growth of the (100) and (110) crystal planes of lithium nickel manganese oxide; (5) The total heating time was controlled to be 10 h. After the microwave heating was turned off, the sintering temperature of the mixed raw materials was controlled to be 930 °C and the synthesis reaction was carried out for 18 h. (6) In the cooling stage, infrared heating is used to raise the temperature to 850°C. After cooling, single crystal lithium nickel manganese oxide synthesized by a multi-stage step-by-step sintering method is obtained. Embodiment 8
[0027] (1) Carbon powder, LiOH·H2O and Ni 0.25 Mn 0.75 O are mixed uniformly according to a molar ratio of 0.02:0.52:1 to obtain a mixed raw material; (2) In the first stage, the temperature is raised to 300°C by infrared radiation heating method, and the heating time is 0.5h. The infrared radiation wavelength is 3μm, the heating rate is 50°C / s, and the instantaneous heat flux density reaches 0.25MW / m 2 , accelerate the discharge of free water and crystal water contained in LiOH·H2O, turn off the infrared radiation heating to reduce the temperature of the mixed raw materials, reduce the temperature to 125℃, and continue to heat up; (3) In the second stage, the carbon powder undergoes an oxidation reaction, releasing a large amount of heat and rapidly raising the temperature of the mixed raw material to 950°C. The heating time is 0.05h, which accelerates the discharge of carbon dioxide gas from the mixed raw material. After the carbon powder reacts, the temperature of the mixed raw material decreases. The temperature drops to 315°C and continues to rise. (4) In the third stage, when the temperature of the mixed raw materials is raised to 650°C, microwave heating is used to rapidly raise the temperature of the mixed raw materials to 950°C for 1 hour, so as to accelerate the growth of the (100) and (110) crystal planes of lithium nickel manganese oxide; (5) The total heating time was controlled to be 15 h. After the microwave heating was turned off, the sintering temperature of the mixed raw materials was controlled to be 820 °C and the synthesis reaction was carried out for 24 h. (6) In the cooling stage, microwave heating is used to raise the temperature to 600°C. After cooling, single crystal lithium nickel manganese oxide synthesized by a multi-stage step-by-step sintering method is obtained. Embodiment 9
[0028] (1) Bioethanol, triethyl phosphate, LiOH·H2O and Ni 0.25 Mn 0.75 (OH)2 was mixed uniformly in a molar ratio of 0.002:0.005:0.25:1 to obtain a mixed raw material; (2) In the first stage, the temperature is raised to 150°C by infrared radiation heating method, and the heating time is 0.5h. The infrared radiation wavelength is 100μm, the heating rate is 40°C / s, and the instantaneous heat flux density reaches 0.15MW / m 2 , accelerate the discharge of LiOH·H2O, Ni 0.25 Mn 0.75 (OH)2 contains free water and crystal water. Turn off the infrared radiation heating to reduce the temperature of the mixed raw materials. When the temperature drops to 80°C, continue to heat up; (3) In the second stage, bioethanol and triethyl phosphate undergo an oxidation reaction, releasing a large amount of heat and rapidly raising the temperature of the mixed raw material to 900°C. The heating time is 0.1h, which accelerates the discharge of carbon dioxide gas from the mixed raw material. After the reaction of bioethanol and triethyl phosphate is completed, the temperature of the mixed raw material decreases. The temperature decreases to 420°C and continues to rise. (4) In the third stage, when the temperature of the mixed raw materials is raised to 760°C, microwave heating is used to raise the temperature to 1000°C for 1 hour to accelerate the growth of the (100) and (110) crystal planes of lithium nickel manganese oxide; (5) The total heating time was controlled to be 8 h. After the microwave heating was turned off, the sintering temperature of the mixed raw materials was controlled to be 850 °C and the synthesis reaction was carried out for 20 h. (6) In the cooling stage, microwave heating is used to raise the temperature to 650°C. After cooling, single crystal lithium nickel manganese oxide synthesized by a multi-stage step-by-step sintering method is obtained. Embodiment 10
[0029] (1) Triethyl phosphate, microcrystalline wax, LiOH·H2O and Ni 0.25 Mn 0.75 O 3.5 Mix evenly according to a molar ratio of 0.03:0.02:0.25:1 to obtain a mixed raw material; (2) In the first stage, the temperature was raised to 250°C by infrared radiation heating, and the heating time was 0.5 h. The infrared radiation wavelength was 50 μm, the heating rate was 20°C / s, and the instantaneous heat flux reached 0.1 MW / m 2 , accelerate the discharge of LiOH·H2O, Ni 0.25 Mn 0.75 (OH)2 contains free water and crystal water. Turn off the infrared radiation heating to reduce the temperature of the mixed raw materials. The temperature is reduced to 105°C and the temperature is continued to rise; (3) In the second stage, triethyl phosphate and microcrystalline wax are used to undergo an oxidation reaction, which releases a large amount of heat and rapidly raises the temperature of the mixed raw materials to 700°C. The heating time is 0.2h, which accelerates the discharge of carbon dioxide gas from the mixed raw materials. After the reaction of triethyl phosphate and microcrystalline wax is completed, the temperature of the mixed raw materials decreases to 460°C and continues to rise; (4) In the third stage, when the temperature of the mixed raw materials is raised to 750°C, microwave heating is used to raise the temperature to 1100°C for 0.5 h to accelerate the growth of the (100) and (110) crystal planes of lithium nickel manganese oxide; (5) The total heating time was controlled to be 20 h. After the microwave heating was turned off, the sintering temperature of the mixed raw materials was controlled to be 870 °C and the synthesis reaction was carried out for 18 h. (6) In the cooling stage, infrared heating is used to raise the temperature to 720°C. After cooling, single crystal lithium nickel manganese oxide synthesized by a multi-stage step-by-step sintering method is obtained.
[0030] Comparative Example 1 (1) Li2CO3 and Ni 0.25 Mn 0.75 (OH)2 was mixed uniformly in a molar ratio of 0.25:1 to obtain a mixed raw material; (2) heating to 900°C by electric heating, and performing the synthesis reaction at 900°C for 16 hours; (3) After cooling, single crystal lithium nickel manganese oxide is obtained.
[0031] Comparative Example 2 (1) Triethyl phosphate, Li2CO3 and Ni 0.25 Mn 0.75 (OH)2 was mixed uniformly in a molar ratio of 0.003:0.25:1 to obtain a mixed raw material; (2) The temperature was raised to 300°C by infrared radiation heating method, the heating time was 0.5h, the infrared radiation wavelength was controlled to 20μm, the heating rate was 40°C / s, and the instantaneous heat flux density reached 0.3MW / m 2 , accelerate the discharge of Ni 0.25 Mn 0.75 (OH)2 contains free water and crystal water; turn off the infrared radiation heating to reduce the temperature of the mixed raw materials, and the temperature is reduced to 115°C, and the temperature is continued to rise; (3) When the temperature of the mixed raw material rises to 900°C, the temperature of the mixed raw material is controlled to be 900°C and the synthesis reaction is carried out for 16 hours; (4) In the cooling stage, infrared heating is used to raise the temperature to 800°C. After cooling, single crystal lithium nickel manganese oxide is obtained.
[0032] The specific surface areas of the high voltage lithium nickel manganese oxide positive electrode materials prepared in the examples of the present invention and the comparative examples were tested, and the results are shown in Table 1.
[0033] Table 1 is a comparison table of specific surface areas of Examples 1-10 of the present invention and Comparative Examples 1 and 2
[0034] It can be seen from Table 1 that the specific surface areas of Examples 1-10 are significantly smaller than those of Comparative Examples 1 and 2.
[0035] The internal resistance of the powder of the high voltage lithium nickel manganese oxide positive electrode material prepared in the embodiment of the present invention and the comparative example was tested, and the results are shown in 2.
[0036] Table 2 is a comparison table of specific surface areas of Examples 1-10 of the present invention and Comparative Examples 1 and 2
[0037] It can be seen from Table 2 that the internal resistance of the powders of Examples 1-10 is significantly smaller than that of Comparative Examples 1 and 2.
[0038] The compaction density of the high voltage lithium nickel manganese oxide positive electrode materials prepared in the examples of the present invention and the comparative examples was tested, and the results are shown in Table 3.
[0039] Table 3 is a comparison table of compaction density of Examples 1 to 10 of the present invention and Comparative Examples 1 and 2
[0040] It can be seen from Table 3 that the compaction density of Examples 1 to 10 is significantly higher than that of Comparative Examples 1 and 2.
[0041] The positive electrode materials in Example 1, Comparative Example 1 and Comparative Example 2 were made into lithium-ion batteries. The specific method was as follows: 9g of positive electrode material, 0.5g of acetylene black and a polyvinylidene fluoride solution with a solid content of 5% were mixed at room temperature and pressure to form a slurry, which was evenly coated on the surface of aluminum foil to obtain a pole piece. The pole piece obtained in the previous step was dried at 80°C and pressed, and cut into pieces with an area of 1.32cm 2 The circular thin sheet was used as the positive electrode, the pure lithium sheet was used as the negative electrode, and the 1 mol / L LiPF6 ethylene carbonate (EC) and dimethyl carbonate (DMC) solution was used as the electrolyte, where the volume ratio of EC to DMC was 1:1, and then the lithium-ion battery was assembled in a glove box filled with argon.
[0042] The room temperature rate and cycle performance of the prepared lithium-ion battery were tested, and the results are shown in Figure 5 , Figure 5 A comparison chart of the cycle performance of the batteries prepared for Example 1, Comparative Example 1 and Comparative Example 2 of the present invention.
[0043] Figure 5 It is a comparison chart of the cycle performance of batteries made from Example 1, Comparative Example 1 and Comparative Example 2.
[0044] Depend on Figure 5It can be seen that the battery prepared in Example 1 has a 0.2C discharge capacity of 127.7 mAh / g, a 1.0C discharge capacity of 127.2 mAh / g, a 1C / 0.2C ratio of 99.6%, and a 1.0C, 50 cycle capacity retention rate of 98.3%; the battery prepared in Comparative Example 1 has a 0.2C discharge capacity of 125.5 mAh / g, a 1.0C discharge capacity of 124.4 mAh / g, a 1C / 0.2C ratio of 99.1%, and a 1.0C, 50 cycle capacity retention rate of 93.6%; the battery prepared in Comparative Example 2 has a 0.2C discharge capacity of 124.6 mAh / g, a 1.0C discharge capacity of 121.5 mAh / g, a 1C / 0.2C ratio of 97.5%, and a 1.0C, 50 cycle capacity retention rate of 69.0%; the rate performance and cycle performance of Example 1 are better than those of Comparative Example 1 and Comparative Example 2.
[0045] The above embodiments are only used to illustrate the present invention, but not to limit the present invention. Although the present invention is described in detail with reference to the embodiments, it should be understood by those skilled in the art that various combinations, modifications or equivalent substitutions of the technical solutions of the present invention do not depart from the spirit and scope of the technical solutions of the present invention, and should be included in the scope of the claims of the present invention.
Claims
1. A single crystal lithium nickel manganese oxide synthesized by a multi-stage stepped sintering method, characterized in that: The method for preparing single crystal lithium nickel manganese oxide comprises the following steps: (1) mixing a combustion aid, a lithium salt and a lithium nickel manganese oxide precursor uniformly according to a molar ratio to obtain a mixed raw material; (2) In the first stage, infrared radiation heating is used to raise the temperature to T1, and the heating time is t1, so that the mixed raw materials are accelerated to discharge free water and crystal water contained in the mixed raw materials, and the infrared radiation heating is turned off to reduce the temperature of the mixed raw materials; (3) In the second stage, the combustion aid is used to generate an oxidation reaction, which releases a large amount of heat and raises the temperature of the mixed raw materials to T2. The heating time is t2, which accelerates the discharge of carbon dioxide gas from the mixed raw materials. After the reaction is completed, the temperature of the mixed raw materials decreases. (4) In the third stage, microwave heating is used to raise the temperature to T3, and the heating time is t3, so that the growth of the (100) and (110) crystal planes of lithium nickel manganese oxide is accelerated; (5) After turning off the microwave heating, controlling the sintering temperature of the mixed raw materials to carry out the synthesis reaction; (6) In the cooling stage, microwave heating or infrared heating is used to raise the temperature to 800°C. After cooling, single crystal lithium nickel manganese oxide synthesized by a multi-stage step-by-step sintering method is obtained.
2. The single crystal lithium nickel manganese oxide synthesized by the multi-stage stepped sintering method according to claim 1, characterized in that: In the above (1), the molar ratio of the combustion aid, the lithium salt and the lithium nickel manganese oxide precursor is 0.001-0.1:0.48-0.58:
1.
3. The single crystal lithium nickel manganese oxide synthesized by the multi-stage stepped sintering method according to claim 1, characterized in that: In the above (1), the combustion aid is one of bioethanol, biobutanol, phosphate ester, triethyl phosphate, microcrystalline wax, liquid paraffin, liquid resin, polyethylene wax, glycerol, glycerol fatty acid, biodiesel, and carbon powder.
4. The single crystal lithium nickel manganese oxide synthesized by the multi-stage stepped sintering method according to claim 1, characterized in that: In (2), during the infrared heating process, the infrared radiation wavelength is 200 μm-1 μm, the heating rate is 10-80°C / s, and the instantaneous heat flux density is 0.01-1 MW / m 2 , T1 is 150-300℃, t1 is 0.1-1h.
5. The single crystal lithium nickel manganese oxide synthesized by the multi-stage stepped sintering method according to claim 1, characterized in that: In the above (3), the combustion aid heating temperature T2 is 700-950°C, and the heating time t2 is 0.01-0.2h.
6. The single crystal lithium nickel manganese oxide synthesized by the multi-stage stepped sintering method according to claim 1, characterized in that: In the above (4), the microwave heating temperature T3 is 750-1200°C, and the heating time t3 is 0.1-2h.
7. The single crystal lithium nickel manganese oxide synthesized by the multi-stage stepped sintering method according to claim 1, characterized in that: In the above (5), the sintering temperature is 820-980°C, and the synthesis reaction time is 12-24h.
8. The single crystal lithium nickel manganese oxide synthesized by the multi-stage stepped sintering method according to claim 1, characterized in that: The preparation temperature curve presents multiple step-like characteristic peaks, that is, during the heating process, there are multiple stages in which the material temperature rises rapidly and then drops. The total heating time for synthesis is t, the synthesis temperature is T, the first stage time is t1, the maximum temperature is T1, the second stage time is t2, the maximum temperature is T2, the third stage time is t3, and the maximum temperature is T3, satisfying the following relationship: T1×t≥T×t1, T2×t≥T×t2, T3×t≥T×t3, where 2≤n≤3.
9. The single crystal lithium nickel manganese oxide synthesized by the multi-stage stepped sintering method according to claim 8, characterized in that: The total heating time t is 3-20h, and the synthesis temperature T is 600-1200°C.
10. The single crystal lithium nickel manganese oxide synthesized by the multi-stage stepped sintering method according to claim 8, characterized in that: The heating method used in the heating process is one or more of electric heating, infrared radiation heating, microwave heating, combustion aid heating, heat flow heating, and Joule heat heating.
Citation Information
Patent Citations
High voltage lithium cobalt oxide positive electrode material and preparation method therefor
CN105470500A
Spinel material
CN108604673A
Method for pretreatment of ternary material mixture
CN109888269A
Monocrystal lithium-manganese-rich positive electrode material for lithium ion battery and preparation method thereof
CN116632218A
Sodium-ion battery positive electrode material as well as preparation method and application thereof
CN118771474A
Cited By
Method for flash preparation of lithium nickel manganese oxide through cooperation of manganese-rich tailings and waste lithium nickelate
CN120887462A